If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 27x = 88 Solving 7 + 27x = 88 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 27x = 88 + -7 Combine like terms: 7 + -7 = 0 0 + 27x = 88 + -7 27x = 88 + -7 Combine like terms: 88 + -7 = 81 27x = 81 Divide each side by '27'. x = 3 Simplifying x = 3
| 13d=52 | | 525=-0.5x^2+36x-87 | | 12x-10=4x+5 | | 2/5x-5≥3 | | 7-x/10≥12 | | 1.8b=9 | | 1/3p-n | | a-4.2=16.8 | | 3x^2-12+9=0 | | 7-8x/1012 | | 5y-3=2y+1 | | 4a+87b+34c=0 | | 30-8b=-2(1+8b) | | 15x+27=19-31x+8 | | (2/5)a=0 | | 3/4x=110 | | 2x+10=x+8+10 | | Logb=xloga | | (x-97)(x-3)=0 | | x^3-30x+3=0 | | 5a+7b=57 | | 5d-7=13 | | 72.1y= | | 4/9-(7/9-2/9) | | 1/5×10.5 | | 1/7×10.5 | | a^3-6b^2+59c=6 | | 21x^2-12x=-1 | | f(x+7)=x^2+8x+45 | | 9+6x=36 | | 6+5x=456 | | 2senx(cos^2x)-senx=0 |